COMPUTER NETS AND WIRELESS TECHNOLOGIE USING IN THE SUBURBAN PUBLIC AND OUT-PLANT-FREIGHT TRANSPORTATION - Sustekova, Daniela; Knutelska, Marta (Doprava a spoje, 2012)
In this article there are described computer nets and wireless technologie using in the suburban public and out-plant-freight transportation. There is described the management of the suburban publict ransuportation using supporting by IT and connection freight cars with the centre and with the board-computer